2019
DOI: 10.1093/eurheartj/ehz552
|View full text |Cite
|
Sign up to set email alerts
|

Invasive left ventricle pressure–volume analysis: overview and practical clinical implications

Abstract: Ventricular pressure–volume (PV) analysis is the reference method for the study of cardiac mechanics. Advances in calibration algorithms and measuring techniques brought new perspectives for its application in different research and clinical settings. Simultaneous PV measurement in the heart chambers offers unique insights into mechanical cardiac efficiency. Beat to beat invasive PV monitoring can be instrumental in the understanding and management of heart failure, valvular heart disease, and mechanical cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(122 citation statements)
references
References 45 publications
7
105
0
3
Order By: Relevance
“…b Corresponding pressure-volume loops showing left shift with reduction in systolic pressure, and increased stroke volume. Copied with permission from Bastos et al [8] and Schreuder et al [9] circulatory support showed that patients supported with a pVAD had lower in-hospital mortality compared with IABP, despite the observation that patients in this group had more comorbidities [17]. Patients with pVAD also had lower cardiac, vascular, and respiratory complications and their duration of hospital stay was shorter.…”
Section: High-risk Percutaneous Coronary Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…b Corresponding pressure-volume loops showing left shift with reduction in systolic pressure, and increased stroke volume. Copied with permission from Bastos et al [8] and Schreuder et al [9] circulatory support showed that patients supported with a pVAD had lower in-hospital mortality compared with IABP, despite the observation that patients in this group had more comorbidities [17]. Patients with pVAD also had lower cardiac, vascular, and respiratory complications and their duration of hospital stay was shorter.…”
Section: High-risk Percutaneous Coronary Interventionmentioning
confidence: 99%
“…By inflating the balloon immediately after aortic valve closure, diastolic and mean arterial pressures rise and coronary perfusion improves. On the other hand, a vacuum effect-caused by rapid deflation of the balloon just before aortic valve opening-provides a reduction in left ventricle afterload and thereby passively augments cardiac output (CO) [8]. The hemodynamic effect will vary based on the clinical setting and the overall stroke volume.…”
Section: Hemodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of PV loop has been described previously [10]. In brief, the invasive hemodynamic assessments were conducted using a Millar pressure catheter (SPR-838; Millar Instruments, Houston, TX, USA) through the right carotid artery into the LV cavity.…”
Section: Pressure-volume (P-v) Loopmentioning
confidence: 99%
“…Extracorporeal membrane oxygenation (ECMO) is one of the most utilized mechanical circulatory support (MCS) modalities in patients with cardiogenic shock (1). Nonetheless, a major disadvantage of peripheral veno-arterial (V-A) ECMO is the risk of increased left-heart filling pressures, especially in patients with highly reduced ejection fractions (EFs) (2).…”
Section: Introductionmentioning
confidence: 99%